Durum wheat breeding for abiotic stresses resistance: Defining physiological traits and criteria - El Jaafari S. (Durum wheat improvement in the Mediterranean region: New challenges, 2000)
Few criteria have been developed into screening techniques that are applicable to large numbers of genotypes. To be practical, screening techniques should be inexpensive, easily performed, repeatable, and accurate for the selected trait. We have considered morphophysiological mechanisms, which contributes to avoidance of desiccation, maintenance of cell turgor, and increased tolerance to low water potentials. Research results from many sources substantiate that no single criterion is comprehensive in predicting plant resistance to stress. Selection for genotype improvement in stress resistance is possible through the use of physiological parameters: some methods have been developed into screening techniques that may be applicable to large numbers of plants in breeding programs, while others are useful only for limited selections.
Seminar on Durum Wheat Improvement in the Mediterranean Region: New Challenges, 2000/04/12-14, Zaragoza (Spain)